Accuracy of triangular meshes of stone models created from DICOM cone beam CT data - Dimitrios Apostolakis; Georgios Michelinakis; Georgios Kourakis; Emmanuel Pavlakis (SpringerOpen, 2019)
Abstract Background The aim of this study was to assess the theory that CBCT scanners can be used for a subsequent triangular mesh generation which accurately represents the actual stone model. Ten, recently acquired stone models, were used in the present study. The stone models were initially scanned with the Dental Wings 7Series dental scanner. Each stone model was then scanned using a 150-μm voxel resolution in a Planmeca Mid CBCT device with 2 sets of exposure parameters and in a Newtom VG device. The DICOM files were initially imported in Blue Sky Plan implant surgery software, segmented and then imported for computational manipulation in CloudCompare, a dedicated mesh handling software. Results For all CBCTs and for all exposure parameters, the mean (SD) difference was 0.052 (0.011) mm ranging from 0.032 to 0.070 mm with a 95% CI for the population mean of 0.052 ± 0.004 mm. Specifically, the mean (SD) difference for each device/exposure parameter tested was (1) Newtom VG = 0.040 (0.006) mm, (2) Planmeca Mid 90 = 0.057 (0.0066) mm, and (3) Planmeca Mid 80 = 0.059 (0.0063) mm. Conclusions There are differences amongst the CBCT models, whilst different exposure parameters of the same model do not seem to offer a significant advantage. The interaction between the threshold value and the imaging modality as far as the errors are concerned necessitates the careful selection of the right threshold value for the triangular mesh creation.